A case of bone resorption in the mentum caused by hyaluronic acid filler in a patient with skeletal Class II jaw deformity - Takayuki Nakagawa; Shigehiro Ono; Miyuki Sakuma; Yoko Ishida; Kuniko Mizuta; Ryo Uetsuki; Keijyuro Odan; Yuko Shintaku; Masataka Higuchi; Yutaka Matsushita; Shunichi Kojima; Isao Hirata; et al. (Clinical Case Reports)
Key Clinical Message Chin augmentation by hyaluronic acid filler injection rarely causes abnormal bone resorption in the mentum. Thus, when taking the history of a patient with jaw deformity, it is imperative to check the history of treatment of the mentum. Abstract Hyaluronic acid (HA) filler injection is a common procedure in nonsurgical cosmetic chin augmentation. Due to its high biocompatibility and simple injection technique, HA filler injection is a popular procedure. However, adverse events such as allergic reactions and foreign body reactions have been reported in some cases. In this study, we report a case of skeletal Class II jaw deformity in which bone resorption was observed in the mentum after HA filler injection. The purpose of this study is to discuss the indications for HA filler injection in skeletal Class II cases that require orthognathic surgery. The patient was a 30‐year‐old woman. To improve retrusion of the mentum, she has been receiving HA filler injections in the mentum three times every 6 months in the cosmetic surgery clinic since 2015. However, the retrusion of the mentum did not improve, which prompted here to visit the orthodontic clinic. Radiographs and CT revealed bowl‐shaped bone resorption surrounding the foreign bodies in the mentum. She was diagnosed with maxillary protrusion, vertical maxillary excess, mandibular retrusion, and bilateral condylar resorption. Bimaxillary orthognathic surgery (BOGS) and removal of residual HA fillers were planned after completion of the preoperative orthodontic treatment. After BOGS, the foreign bodies were completely removed, and the resorption cavities were filled with excess bone segments from the surgical sites. X‐ray photoelectron spectroscopy analysis of the foreign bodies suggested the presence of HA. One year after the BOGS, no progression of condylar resorption occurred, and bone healing at the mentum had a good prognosis. Therefore, the patient underwent reduction and advancement genioplasty. She was satisfied with her facial profile and occlusal function. Unexpected bone resorption in the mentum caused by HA filler injection is often discovered incidentally. Although, patients may feel hesitant to confess their history of treatment of the mentum, it is important to ensure that they are carefully interviewed.